The Declining Share of Agricultural Employment in the People's Republic of China: How Fast? - Jesus Felipe; Connie Dacuycuy; Matteo Lanzafame (Asian Development Bank (ADB), 2014)
From 1962 to 2013, the People's Republic of China's (PRC's)agricultural employment share declined from 82% to 31%. The transfer of workers out of low-productivity agriculture is a fundamental pillar of the PRC's aspirations to progress and eventually become a high-income economy. We hypothesize that the drivers of this decline have been the increase in income per capita, industrial value added, foreign direct investment, and domestic credit. We use an Autoregressive Distributed Lag Model to test the strong exogeneity of the regressors so that we can use it for forecasting. Results indicate that the share of employment in agriculture in the PRC will decline to about 24% by 2020, the end of the 13th Five-Year Plan (2016-2020). We also estimate that the PRC's employment share will reach 5%, the share observed in today's rich economies, by 2042-2048.
hdl:11540/4215
Keywords: O13; O53; Q10; 330; agricultural employment; People's Republic of China; structural transformation; Landwirtschaft; Arbeitskräfte; Strukturwandel; China